European Beech (Fagus sylvatica L.): Quasi-Virgin Forest Stand of the Gorgany Mts.: Structure, Vascular Plants Diversity, Health Conditions - Yuriy Shparyk; Ivan Danylyk; Oleksandr Kuzyarin; Ivan Senchak; Nazar Kruk (Наукові праці Лісівничої академії наук України)
The basic priority in the activities of the institutions of the nature reserve fund of Ukraine is the natural ecosystems’ biodiversity preservation, and its implementation should ensure the restoration of their natural structure and the prevention of invasive species’ penetration into ecosystems and the fight against them. In the Gorgany Mts. (Ukrainian Carpathians), all PZF institutions are located in the forest fund, and the virgin and quasi-virgin forests are standards of the natural structure, condition and vascular plants diversity for local ecosystems. Therefore, the study of the structure, diversity of vascular plants and health conditions of European beech quasi-virgin forests will provide an opportunity to develop environmental protection measures for restoring the biodiversity of the local beech forests. 14 experimental plots in the Gorgan beech quasi-virgin forests were studied in moist fairly fertile conditions of Norway spruce (Picea abies) – Silver fir (Abies alba) –European beech forest type in the territory of the Syniohora NNP. The studies were carried out using traditional forest inventory methods in permanent and temporary experimental plots. The vascular plants were identified using the collections of the Carpathian Ecology Institute and the State Natural History Museum of the National Academy of Sciences of Ukraine. It has been established that the 190-year-old beech quasi-virgin forests of Gorgan are 3-storeyed spruce-fir-beech (Norway spruce – Silver fir – European beech) primary uneven-aged stands with the following parameters: high productivity; normal number of trees; a large stock of growing timber; a low stock of dead-standing trees; a significant stock of dead down trees; a large proportion of trees with damaged crowns; close to the average values of IUFRO classes; successful natural regeneration. The coefficient of variation of these parameters ranges from 50% for the number of trees, 15% for average height of stands, and their variability is, in general, significant. The first storey of these forests is a spruce-fir-beech stand with seven trees species, which has the following average parameters: age ≈ 190 years, the number of trees ≈ 170 ha-1, diameter ≈ 62 cm, height ≈ 35 m, the total basal area ≈ 50 m2/ha, the volume of live trees ≈ 760 m3/ha, the volume of dead-standing trees ≈ 4 m3/ha, the proportion of damaged trees (mainly trunks) ≈ 56%. The second storey is also a spruce-fir-beech stand, but with six species and with significantly lower parameters, especially diameter (≈ 35 cm) and the volume of live trees ≈ 160 m3/ha. The third storey is similar to the second one, but with even lower average parameters, especially the volume of live trees ≈ 40 m3/ha. The exception is the number of trees in the third storey – it is the largest than in all the other storeys since the distribution of trees by diameter in quasi-virgin forests has a descending character. The stock of dead-standing trees is formed mainly by beech with the participation of spruce, and the stock of dead down trees is formed by spruce with the participation of beech. The number of viable natural regeneration is 15.7 thousand pcs/ha and is almost equally divided between European beech, sycamore and silver fir. The vascular plants diversity of these forests is formed by 51 species: 7 species of trees, 5 – shrubs, 3 – subshrubs, 36 – herbs. The variability of the height of grasses and their share in the plant association is average (v>20%).